2017
DOI: 10.18632/oncotarget.20319
|View full text |Cite
|
Sign up to set email alerts
|

IL-23R and IL-17A polymorphisms correlate with susceptibility of ankylosing spondylitis in a Southwest Chinese population

Abstract: The association between the IL-23R and IL-17A polymorphisms and ankylosing spondylitis (AS) in the Southwest Chinese Population is still unclear. The purpose of this study is to detect the association between IL-23R and IL-17A polymorphisms and AS. A case–control study consisting of 486 AS patients and 480 healthy controls was performed. We used the high-resolution melting methods (HRM) to genotype five selected single nucleotide polymorphisms (SNPs), rs6693831, rs7517847, rs1884444, rs10889677 in the IL-23R g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Single nucleotide polymorphisms identified in the IL-17 signalling pathway that have been linked to axial spondyloarthritis and psoriatic arthritis. a Significant association shown in European but not Asian populations204; b No risk associated with this SNP shown in certain studies204–206; c No risk associated with this SNP shown in certain studies207; d SNP can be associated with risk or protection depending on the specific mutation. AS, ankylosing spondylitis; IL-1R2, interleukin 1 receptor; IL-6R, interleukin 6 receptor; IL17R, interleukin receptors; PsA, psoriatic arthritis; SNP, single nucleotide polymorphism.…”
Section: Role Of Il-17a In Spamentioning
confidence: 99%
“…Single nucleotide polymorphisms identified in the IL-17 signalling pathway that have been linked to axial spondyloarthritis and psoriatic arthritis. a Significant association shown in European but not Asian populations204; b No risk associated with this SNP shown in certain studies204–206; c No risk associated with this SNP shown in certain studies207; d SNP can be associated with risk or protection depending on the specific mutation. AS, ankylosing spondylitis; IL-1R2, interleukin 1 receptor; IL-6R, interleukin 6 receptor; IL17R, interleukin receptors; PsA, psoriatic arthritis; SNP, single nucleotide polymorphism.…”
Section: Role Of Il-17a In Spamentioning
confidence: 99%
“…Three single nucleotide polymorphisms (SNPs) in genes that encode inflammatory cytokines have been associated with AS, in a previous study by our research group ( TNF rs1800629, IL17A rs2275913, and IL17F rs763780) ( 6 ). These polymorphisms can interfere with the level of production of these cytokines and contribute to the development of AS ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…[12,21] The expression of MMP genes were found to be associated with several proinflammatory cytokines, such as tumor necrosis factor-alfa (TNF-α) and IL-17. [22,23] Recent studies have indicated that single-nucleotide polymorphisms (SNPs) in IL and ERAP are associated with an increased risk of AS, [24,25] while few studies concentrated on the correlation between SNPs in MMP and AS. In addition, there is no report on the relationship between MMP-8 and AS.…”
Section: Introductionmentioning
confidence: 99%